Sleep and Bone Density: A Study on Postmenopausal Indonesian Women - Shafira Irmayati; Muhammad Reagan; Legiran Legiran (HM Publisher, 2019)
Background: Low bone density has been known as one of the factors that increased fracture risk. Aging, estrogen deficiency, low BMI, and inadequate calcium intake are known factors that contribute to decreased bone density. Other than the known factors, some research show that sleep duration can also lower bone density. Sleep affects bone density in a way that it causes increased level of cortisol, proinflammatory cytokine, and decreased in physical activity. Method: This study is an observational analytic study with cross-sectional design. It is conducted on menopausal patients that has been examined with bone mineral densitometry at Poliklinik Reumatologi Penyakit Dalam RSUP Dr. Mohammad Hoesin Palembang in November 2017 to Oktober 2018. Samples are collected using total sampling technique. Results: From 93 subjects that participated in this study, 20,4% of them had osteopenia, and 51,6% had osteoporosis. Patients with low bone density, mainly slept for 6 to 8 hours at night per day, 30 minutes of nap per day, and has a total sleep duration for less than 8 hours each day. This study shows no significant association between night-time sleep, daytime napping, and total sleep duration with bone density (p value = 0,168, p value = 0,831, p value = 0,984). Analysis on other risk factors show significant association between body mass index and low bone density (p value = 0,002). Conclusion: There are no significant association between sleep duration and bone density in menopausal patients at Poliklinik Reumatologi RSUP Dr. Mohammad Hoesin Palembang.